Implementasi Prinsip - Prinsip Manajemen Mutu di SMA Negeri 3 Pangkalan Bun - Sukirno Sukirno; Siminto Siminto (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
The purpose of this study is to determine how the implementation of quality management principles in educational institutions of SMA Negeri 3 Pangkalan Bun can be carried out well and have an impact on improving the quality of education. This study was conducted by reviewing or reviewing the literature in depth and conducting case studies. The results of this study illustrate that the implementation of quality management principles in SMA Negeri 3 Pangkalan Bun effectively can create a better learning environment, improve the quality of education, and optimize the involvement of all stakeholders.